The "Cult of True Womanhood" and American Catholic Sisters: An Example of Creative Subversion - Thompson, Margaret Susan (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación)

(untitled) (Faculty of Education, Queen's University, 2021)
Barbara Welter concludes her pathbreaking article, “The Cult of True Womanhood, 1820-1860,” by declaring that “[Various forces in their lives] … called forth responses from woman, which differed from those she was trained to believe were hers by nature and divine decree. The very perfection of True Womanhood, moreover, carried within itself the seeds of its own destruction. For if woman was so very little less than the angels, she should surely take a more active part in running the world, especially since men were making such a hash of things” [174]. Traditionally, in both Welter’s original work and the many efforts that have subsequently followed, the living out of “True Womanhood” and the creative subversion it unintentionally inspired have been understood almost exclusively in either secular or Protestant contexts. This article explores the role of Catholic education by sisters in both reinforcing and undermining Victorian gender roles, and specifically analyzes the contributions of Catholic women religious to the complex and subversive process that Welter suggested. It analyzes the cultural and religious tensions that characterized nineteenth-century Catholic women’s education, as well as the women’s agency that, however inadvertently, it came to empower.